Evaluation of Second-Generation Lipophosphonoxins as Antimicrobial Additives in Bone Cement - Zborníková, Eva; Gallo, Jiří; Večeřová, Renata; Bogdanová, Kateřina; Kolář, Milan; Vítovská, Dragana; Do Pham, Duy Dinh; Pačes, Ondřej; Mojr, Viktor; Šanderová, Hana; Ulrichová, Jitka; Galandáková, Adéla; et al. (ACS omega, 2020)
Successful surgeries involving orthopedic implants depend on the avoidance of biofilm development on the implant surface during the early postoperative period. Here, we investigate the potential of novel antibacterial compounds-second-generation lipophosphonoxins (LPPOs II)-as additives to surgical bone cements. We demonstrate (i) excellent thermostability of LPPOs II, which is essential to withstand elevated temperatures during exothermic cement polymerization; (ii) unchanged tensile strength and elongation at the break properties of the composite cements containing LPPOs II compared to cements without additives; (iii) convenient elution kinetics on the order of days; and (iv) the strong antibiofilm activity of the LPPO II-loaded cements even against bacteria resistant to the medicinally utilized antibiotic, gentamicin. Thus, LPPOs II display promising potential as antimicrobial additives to surgical bone cements.